Education for entrepreneurship: a proposal for higher education based on Disney's creative strategy - Gonçalves, Vitor (2017)
In the last years, the Polytechnic Institute of Bragança (Portugal) has included in its courses curricular units in the scope of Education for Entrepreneurship. These curricular units recognize in the student the need of skills and competences to create a project more creative, innovative, distinctive and sustainable and, consequently, an entrepreneurial spirit based on those competencies to elaborate a different project or business plan. In addition, students of courses that do not include this type of curricular units can attend a short course to generate his own business plan. This short course is called Poliempreende and is promoted by the institution's entrepreneurship office. In the context of formal education, students, after acquiring the essential entrepreneurship skills and tools for generating and describing a business model or project, were challenged to generate business or project ideas, particularly in the areas and competencies of their course. Generally speaking, first, the workgroups used the Disney’s Creative Strategy in order to explore their business idea from a number of complementary points of view, e.g. according to three different Disney’s roles: the Dreamer, the Designer, and the Critic. Then they used the Business Model Canvas proposed by Alexander Osterwalder to present the business idea. Finally they described the business plans, filling out the corresponding models proposed by the Agency for Competitiveness and Innovation or the project model in accordance with the Project Management Body of Knowledge. Finally, the evaluation of this experience was based on an observation grid used by the teacher and on an individual inquiry and reflection presented by the students. This article aims to present the planning process of a micro-business or a project and corresponding execution and evaluation, thus contributing to the promotion of education for entrepreneurship and consequently to the improvement of employability issues and trends.